5(3-w)+3=-3(w-4)-8

Simple and best practice solution for 5(3-w)+3=-3(w-4)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3-w)+3=-3(w-4)-8 equation:


Simplifying
5(3 + -1w) + 3 = -3(w + -4) + -8
(3 * 5 + -1w * 5) + 3 = -3(w + -4) + -8
(15 + -5w) + 3 = -3(w + -4) + -8

Reorder the terms:
15 + 3 + -5w = -3(w + -4) + -8

Combine like terms: 15 + 3 = 18
18 + -5w = -3(w + -4) + -8

Reorder the terms:
18 + -5w = -3(-4 + w) + -8
18 + -5w = (-4 * -3 + w * -3) + -8
18 + -5w = (12 + -3w) + -8

Reorder the terms:
18 + -5w = 12 + -8 + -3w

Combine like terms: 12 + -8 = 4
18 + -5w = 4 + -3w

Solving
18 + -5w = 4 + -3w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '3w' to each side of the equation.
18 + -5w + 3w = 4 + -3w + 3w

Combine like terms: -5w + 3w = -2w
18 + -2w = 4 + -3w + 3w

Combine like terms: -3w + 3w = 0
18 + -2w = 4 + 0
18 + -2w = 4

Add '-18' to each side of the equation.
18 + -18 + -2w = 4 + -18

Combine like terms: 18 + -18 = 0
0 + -2w = 4 + -18
-2w = 4 + -18

Combine like terms: 4 + -18 = -14
-2w = -14

Divide each side by '-2'.
w = 7

Simplifying
w = 7

See similar equations:

| 1+qwertyuiop=9 | | x^2-XM-m^2=0 | | 3x+2x+1x+12=18 | | 0.90x+0.05(2-x)=0.10(92) | | 28-15= | | (-54)+17= | | 5m^2+12m-200=-3m | | -5b+3b-10=2 | | -x+5=t-19 | | Vm=9 | | 5+5x+6x-4=180 | | 3p-7q+14p-8q=0 | | 8[6-(-9x-4)]=648x+336 | | 7x-8yi=21+40i | | 1/4x+3=-1 | | 5(b+1)=5b-3 | | 2*3*14*r=94.2 | | (9+9)(10-1)(2)= | | 11p^2+63p+50=4p^2-6 | | ry+sy=tfory | | M+n+p=q | | 3x^2+5xy-2y^2=0 | | 24w=6 | | (-99)+52= | | 5s+7=4x+7 | | g(1+5m)=2x^2+18-14 | | 3x-11/5=-4 | | 4-d=d-4 | | (1+5)(3)+(7)(2)= | | 7/9+(-3/5) | | 5(v-3)-2v=-30 | | 10x^8=40 |

Equations solver categories